Implementation of P5 learning in Islamic religious education at SMK Negeri 8 Medan - Fitri, Humaira Nurwani; Abrianto, Danny (Universitas Syiah Kuala, 2025)
The P5 program aims to shape students' character and develop Pancasila learners who can behave in accordance with Pancasila values. Students serve both as subjects and objects in the implementation of the P5 learning method (Project for Strengthening the Pancasila Student Profile). This study focuses on the application of P5 learning in Islamic Religious Education at SMK Negeri 8 Medan. The objectives are to describe the implementation of P5 in Islamic Religious Education, methods used to strengthen character aligned with the Pancasila Student Profile, and the supporting and inhibiting factors in the P5 implementation. This research employs a field research method with a qualitative approach, which is descriptive and analytical in nature. It intensively examines the background, current situation, social interactions, groups, and individuals. The findings reveal that P5 learning enhances Pancasila values in everyday life, such as faith in God Almighty, noble character, knowledge, creativity, and student independence. In conclusion, P5 learning positively affects students by increasing creativity, independence, and motivation to learn Islamic Religious Education in Class X Boga 5.